(untitled) (Research, Society and Development, 2023)
Genetics is a vast area, covering different segments of society, thus having an interdisciplinary character. It is present in applied society in agricultural sciences, ecology, health, it covers the study of ethics, mathematical knowledge, among others. However, learning in genetics is low and is linked to many challenges. The present work has the objective of highlighting the main challenges, at the same time demonstrating the measures and pedagogical strategies employed in the teaching of genetics to effect the quality of learning at secondary level. To this end, a brief bibliographical survey was carried out in the Capes journal base and in Google Scholar, considering the period from 2017 to 2021 and using the following research descriptors: teaching genetics, high school, importance, methodology, challenges, problems, learning difficulties, new methodologies. The research is of a bibliographic and qualitative nature. Articles were found that discussed the problems and learning in genetics, where they showed that the low training of teachers, traditional methodologies, use of unattractive didactic resources such as the book, are the main reasons. Thus, the research demonstrated that in order to address the problem, it will be necessary for teachers to carry out continuous training to improve their practices and their own learning in genetics, and it brings a new opportunity for study in terms of learning the bases for teaching genetics in the fundamental.